2014
DOI: 10.1586/14779072.2014.953483
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers in the diagnosis of acute coronary syndromes: the role of circulating miRNAs

Abstract: Cardiovascular disease, in particular acute coronary syndromes (ACS), is still one of the leading causes of death in industrialized countries. ACS including ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI) and unstable angina pectoris (UA) are associated with lower mortality if diagnosed early. The diagnosis is based on clinical symptoms, ECG and circulating biomarker-level changes. Recent studies have shown that there are alternatives to the known biomarkers such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In the cardiovascular system, miRNAs have been shown to play crucial roles in pathophysiological conditions, such as endothelial dysfunction, inflammation, apoptosis, and angiogenesis . Several studies highlighted the potential of circulating miRNAs as diagnostic and prognostic biomarkers in ACS . Yet, most of these studies used samples taken at the time of reperfusion to determine miRNAs, rather than samples taken upon initial admission to the Emergency Unit, when diagnostic uncertainty is most evident.…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, miRNAs have been shown to play crucial roles in pathophysiological conditions, such as endothelial dysfunction, inflammation, apoptosis, and angiogenesis . Several studies highlighted the potential of circulating miRNAs as diagnostic and prognostic biomarkers in ACS . Yet, most of these studies used samples taken at the time of reperfusion to determine miRNAs, rather than samples taken upon initial admission to the Emergency Unit, when diagnostic uncertainty is most evident.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that miRNAs are involved in the pathogenesis of various cardiovascular diseases, including MI, heart failure, atherosclerosis and acute coronary syndromes (20,21). In addition, miRNAs have been shown to be key regulators of cardiac development, angiogenesis and vascular development (22). A previous study reported that miRNAs circulated in the blood of patients with cardiovascular diseases in a stable form (23); therefore, due to this stability, circulating miRNAs may serve as novel biomarkers for the diagnosis of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs emerge as promising sensitive and specific biomarkers for cardiovascular disease. 19 , 20 A recent study proved certain circulating miRNAs can distinguish TTC from STEMI patients. 21 In addition, the significant up-regulation of the stress- and depression-related miRNAs suggests a close connection of TTC with neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%